Brain and Health Informatics International Conference, BHI 2013, Maebashi, Japan, October 29-31, 2013. Proceedings - Imamura, Kazayuki; Usui, Shiro; Shirao, Tomoaki; Kasamatsu, Takuji; Schwabe, Lars.; Zhong, Ning.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the International Conference on Brain and Health Informatics, BHI 2013, held in Maebashi, Japan, in October 2013. The 33 revised full papers presented together with 8 workshop papers and 12 special session papers were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections on thinking and perception-centric Investigations of human Information processing system; information technologies for curating, mining, managing and using big brain/health data; information technologies for healthcare; data analytics, data mining, and machine learning; and applications. The topics of the workshop papers are: mental health with ICT; and granular knowledge discovery in biomedical and active-media environments; and the topics of the special sessions are: human centered computing; neuro-robotics; and intelligent healthcare data analytics.
Thinking and perception-centric investigations of human Information processing system -- Information technologies for curating, mining, managing and using big brain/health data -- Information technologies for healthcare -- Data analytics, data mining, and machine learning -- Applications -- Mental health with ICT -- Granular knowledge discovery in biomedical and active-media environments -- Human centered computing -- Neuro-robotics -- Intelligent healthcare data analytics.
Keywords: Computer science; Medical records -- Data processing; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Health Informatics; Information Systems and Communication Service